Performance evaluation of vertical handoff in fourth generation (4G) networks model - 'Aini Syuhada, Md Zain; Mahamod, I.; Wan Nur Suryani Firuz, Wan Ariffin (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org